Profile of scientific reasoning skill and ecological intelligence of pre-service biology teacher - A Putra; T Hidayat; A Rahmat; S Redjeki (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aims to determine the profile of students' scientific reasoning and ecological intelligence skills. The research method used is mixed methods with good performance by using both quantitative and qualitative analysis. The design used in this research is embedded design. This study includes a validator consisting of material experts and learning device experts, 1 high education practitioner, and experiments with a sample of 20 students. The instruments used include questionnaires, observations, interviews, and tests. The experiment used a class of 20 students. Data analysis and processing techniques used during the research are descriptive analysis, percentage technique, and independent sample variable test. The procedure in this research is to do the necessary things in the execution of research such as preparing questionnaire format, observation, teacher and student interview, and experiment with pretest and posttest for scientific reasoning skill and ecological intelligent on learning environmental knowledge. Data collection through interviews, observation and documentation, and test result data. The result of the research shows the profile of students' scientific reasoning ability in the biology education program of the University of Muhammadiyah Bengkulu, including deductive and inductive reasoning with the percentage of "good" category achievement of 73% and the proficiency profile of ecological intelligence of "excellent".